Thermoplastic elastomer with advanced hydrophilization and bonding performances for rapid (30 s) and easy molding of microfluidic devices. Issue 15 (28th June 2017) - Lachaux, Julie; Alcaine, Clara; Gómez-Escoda, Blanca; Perrault, Cécile M.; Duplan, David Olea; Wu, Pei-Yun Jenny; Ochoa, Iñaki; Fernandez, Luis; Mercier, Olaf; Coudreuse, Damien; Roy, Emmanuel
Abstract : SOFT THERMOPLASTIC material (USP Class VI). Abstract : One of the most important areas of research on microfluidic technologies focuses on the identification and characterisation of novel materials with enhanced properties and versatility. Here we present a fast, easy and inexpensive microstructuration method for the fabrication of novel, flexible, transparent and biocompatible microfluidic devices. Using a simple hot press, we demonstrate the rapid (30 s) production of various microfluidic prototypes embossed in a commercially available soft thermoplastic elastomer (sTPE). This styrenic block copolymer (BCP) material is as flexible as PDMS and as thermoformable as classical thermoplastics. It exhibits high fidelity of replication using SU-8 and epoxy master molds in a highly convenient low-isobar (0.4 bar) and iso-thermal process. Microfluidic devices can then be easily sealed using either a simple hot plate or even a room-temperature assembly, allowing them to sustain liquid pressures of 2 and 0.6 bar, respectively. The excellent sorption and biocompatibility properties of the microchips were validated via a standard rhodamine dye assay as well as a sensitive yeast cell-based assay. The morphology and composition of the surface area after plasma treatment for hydrophilization purposes are stable and show constant and homogenous distribution of block nanodomains (∼22° after 4 days). These domains, which are evenly distributed on the nanoscale, therefore account for the uniform and convenient surface of a " microfluidic scale device ". To our knowledge, this is the first thermoplastic elastomer material that can be used for fast and reliable fabrication and assembly of microdevices while maintaining a high and stable hydrophilicity.